Lymphangiogenesis in abdominal aortic aneurysm. Issue 7 (3rd May 2013) - Scott, D. J. A.; Allen, C. J.; Honstvet, C. A.; Hanby, A. M.; Hammond, C.; Johnson, A. B.; Perry, S. L.; Jones, P. F.
<x xml:space="preserve">Abstract</x> Background Ongoing angiogenesis is implicated in the inflammatory environment that characterizes abdominal aortic aneurysm (AAA). Although lymphangiogenesis has been associated with chronic inflammatory conditions, it has yet to be demonstrated in AAA. The aim was to determine the presence of lymphangiogenesis and to delineate the relationship between inflammation and neovascularization in AAA tissue. Methods AAA samples and preoperative computed tomography images were obtained from patients undergoing elective AAA repair. Control samples were age‐matched abdominal aortic tissue. Specific immunostains for blood vessels (CD31, CD105), lymphatic vessels (D2‐40), vascular endothelial growth factor (VEGF) A and VEGF receptor (VEGFR) 3 allowed characterization and quantitation of vasculature. Results The AAA wall contained high levels of inflammatory infiltrate; microvascular densities of blood (P < 0·001) and lymphatic (P = 0·003) vessels were significantly increased in AAA samples compared with controls. Maximal AAA vascularity was observed in inflammatory areas, with vessels that stained positively for CD31 (ρ = 0·625, P = 0·017), CD105 (ρ = 0·692, P = 0·009) and D2‐40 (ρ = 0·675, P = 0·008) correlating positively with the extent of inflammation. Increased VEGFR‐3 and VEGF‐A expression was also evident within inflammatory AAA areas. Conclusion These findings demonstrated lymphatic vessel involvement in end‐stage AAA disease, which was associated with the degree of inflammation, and confirmed the involvement of neovascularization.